Do the Integrated Health Posts Have Contextual Effect on Birth Weight? A Multilevel Evidence from Situbondo, East Java - Eti Kuswandari; Harsono Salimo; Yulia Lanti Retno Dewi (Journal of Maternal and Child Health, 2020)
Background: Low birth weight babies (LBW) are sensitive indicators of socioeconomic condi